Nano-SO42–/TiO2 Catalyzed Eco-Friendly Esterification of Dicarboxylic Acids - Ji, Xianbing; Chen, Yinxia; Shen, Zuoyuan (Asian Journal of Chemistry, 2014)
Nano-SO42–/TiO2 was prepared by wet impregnation method. The structure and properties of the prepared nano-SO42–/TiO2 catalyst was characterized by XRD, SEM, TEM and BET analysis. The catalytic activities of the catalysts were tested by the esterification of sebacic acid with 2-ethyl hexanol and a series of other dicarboxylic acid. The influence factors on the reaction, such as the catalyst calcination temperature, reaction temperature/time and the molar ratio of acid to alcohol were extensively explored. Nano-SO42–/TiO2 prepared exhibited much higher catalytic activity in esterification reactions. By applying the optimized reaction condition, i.e. 160 ºC, 2 h, 5 wt % nano-SO42–/TiO2 with a 1:3 molar ratio of sebacic acid to 2-ethyl hexanol, higher than 99 % isolated of the desired ester could be obtained.